Evaluating the efficacy of a two- site ('COVID-19' and 'COVID-19- free') trauma and orthopaedic service for the management of hip fractures during the COVID-19 pandemic in the UK. (June 2020) - Chui, K.; Thakrar, A.; Shankar, S.
No abstract available